Photodegradation of nitrobenzene using cobalt modified zinc oxide particles - Liman, Muhammad Gidado; Abdullah, Abdul Halim; Hussein, Mohd. Zobir; Zainal, Zulkarnain (Chemic Publishing Company, 2014)
This paper reports the synthesis and modification of zinc oxide, ZnO nanoparticles from zinc nitrate hexahydrate, citric acid and cobalt nitrate hexahydrate, using polyethylene glycol as a surfactant via a combination of hydrothermal and sol-gel methods. The sample was calcined at 500 °C for 2 h. The characterization of the nanoparticles was done using XRD, TEM, FESEM and BET surface area measurement analysis. The photodegradation study was run for 2 h in an improvised photoreactor using an 18 W visible light source. The extent of photodegradation and mineralization was conducted using UV-visible spectroscopy, COD and TOC measurements. The band gap energy was measured using UV-visible spectroscopy and it was found to be 3.22 eV. The XRD results confirmed the ZnO nanoparticles of being hexagonal with Wurtzite structure. The morphology as revealed by TEM and FESEM showed the samples to be spherical in shape and with particle size less than 100 nm. The surface area of the catalyst as measured via BET is 17.566 m2/g. After 2 h of degradation 80.39 % of nitrobenzene was removed. The COD and TOC results removal reach 79 and 66 %, respectively. From the results it could be understood that ZnO synthesized and modified using cobalt nitrate could be an effective candidate for wastewater treatment. - See more at: http://www.asianjournalofchemistry.co.in/user/journal/viewarticle.aspx?ArticleID=26_27_67#sthash.UcbNjrzp.dpuf